Psychosocial morbidity in women with abnormal cervical cytology managed by cytological surveillance or initial colposcopy: longitudinal analysis from the TOMBOLA randomised trial. Issue 4 (14th June 2016) - Fielding, S.; Rothnie, K.; Gray, N. M.; Little, J.; Cruickshank, M. E.; Neal, K.; Walker, L. G.; Whynes, D.; Cotton, S. C.; Sharp, L.; ,
Abstract: Objective: To compare psychosocial outcomes (follow‐up related worries and satisfaction with follow‐up related information and support) over 30 months of two alternative management policies for women with low‐grade abnormal cervical cytology. Methods: Women aged 20–59 years with low‐grade cytological abnormalities detected in the National Health Service Cervical Screening Programme were randomised to cytological surveillance or initial colposcopy. A total of 3399 women who completed psychosocial questionnaires at recruitment were invited to complete questionnaires at 12, 18, 24 and 30 months. Linear mixed models were used to investigate differences between arms in the two psychosocial outcomes. Each outcome had a maximum score of 100, and higher scores represented higher psychosocial morbidity. Results: On average, over 30 months, women randomised to colposcopy scored 2.5 points (95%CI −3.6 to −1.3) lower for follow‐up related worries than women randomised to cytological surveillance. Women in the colposcopy arm also scored significantly lower for follow‐up related satisfaction with information and support (−2.4; −3.3 to −1.4) over 30 months. For both outcomes, the average difference between arms was greatest at 12th‐ and 18th‐month time points. These differences remained when the analysis was stratified by post‐school education. Conclusions: Women with low‐grade cytology, irrespective of their management, have substantial initial psychosocial morbidity that reduces over time. Implementation of newer screening strategies, which include surveillance, such as primary HPV screening, need to consider the information and support provided to women. © 2016 The Authors. Psycho‐Oncology published by John Wiley & Sons Ltd.